Suitability of Using Herbs as Functional Ingredients in Thai Commercial Snacks - Wiwat Wangcharoen; Tipvanna Ngarmsak; Brian H. Wilkinson (Agriculture and Natural Resources, 2002)
Forty-three Thai consumers were informed about the physical properties and medicinal uses of selected Thai herbs prior to asked to make a decision on which of 14 functional herbs could be used in 7 different types of Thai commercial snack foods. Thirty-eight New Zealanders evaluated the suitability of 8 Thai herbs together with other 8 herbs grown in New Zealand. The results of both Thai and New Zealand respondents showed that functional herbs could be added to prawn crackers, dried squid and dried fish snacks, puffed snacks and potato chips rather than nuts or popcorn. The suitable Thai herbs selected by Thais were pepper, holy basil and garlic. For New Zealanders, the suitable NZ herbs were chives and parsley, and the more suitable Thai herbs were garlic, lemon grass, pepper, and ginger.